ENTRENCHING REALIST EVALUATION IN EDUCATIONAL RESEARCH METHODS IN THE AWAKE OF MIXED METHODOLOGY - Amukowa, Wycliffe (British International Journal of Education And Social Sciences, 2021)
The choice of either Quantitative or Qualitative research methods or a mixture of both (Mixed Methods) presents a researcher’s construction of the reality he or she purposes to investigate. The central element in mixed methods is the use of both quantitative and qualitative approaches on one or more of the levels of epistemology, methodology and methods. This rests on the logic that methods, methodologies and paradigms are strongly linked. This construction of research could perhaps get lessons from Realist evaluation approach. Realist evaluation has its origin; Realism. Realism is a school of philosophy. It was developed to sit between positivism and constructivism. Positivism holds that there is such a thing as the real world, which we can directly observe and about which we can derive facts; while constructivism argues that since all our observations are shaped and filtered through human senses and the human brain, it is not possible to know for certain what the nature of reality is. All evaluation approaches – consciously or unconsciously – reflect deep philosophical assumptions. Research is basically evaluation and therefore this paper draws the implications of Realist Evaluation facets on Educational Research.
Keywords: Education; Realism; Research; Evaluation